Persistent Cigarette Smoking Attenuates Plaque Stabilization in Response to Lipid-Lowering Therapy: A Serial Optical Coherence Tomography Study - Zhang, Xiling; Peng, Xiang; Li, Lulu; Yu, Huai; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study aimed to investigate the effect of smoking on morphological changes in non-culprit plaques in acute coronary syndrome (ACS) patients at 1 year after percutaneous coronary intervention (PCI), using optical coherence tomography (OCT). Background: Cigarette smoking is an important risk factor for coronary artery disease. However, the reasons for the high risk of re-infarction and worsened health among patients who continue to smoke after PCI remain unclear. Methods: A total of 129 non-culprit plaques were identified from 97 ACS patients who underwent OCT imaging at the time of PCI and at 1-year follow-up. Patients were divided into the following three groups according to their smoking status at 1-year follow-up: persistent smoking group (n = 26), smoking cessation group (n = 29), and nonsmoking group (n = 42). Medical history, serum cholesterol level, coronary angiography data, and OCT-determined plaque morphology were analyzed among the three groups. Results: Relative to baseline levels, the total cholesterol and low-density lipoprotein cholesterol levels significantly decreased in all three groups at 1-year follow-up after statin therapy (p < 0.05). The persistent smoking group had a relatively smaller fibrous cap thickness (FCT) and a higher incidence of thin-cap fibroatheroma (TCFA) than the other two groups at 1-year follow-up (p < 0.05), although the FCT increased and the incidence of TCFA decreased in all three groups. Conclusions: Persistent smoking is associated with an attenuated effect of statin therapy on plaque stabilization in ACS patients.